Advances in Chemical Priming to Enhance Abiotic Stress Tolerance in Plants. (23rd September 2020) - Sako, Kaori; Nguyen, Huong Mai; Seki, Motoaki
Abstract: Abiotic stress is considered a major factor limiting crop yield and quality. The development of effective strategies that mitigate abiotic stress is essential for sustainable agriculture and food security, especially with continuing global population growth. Recent studies have demonstrated that exogenous treatment of plants with chemical compounds can enhance abiotic stress tolerance by inducing molecular and physiological defense mechanisms, a process known as chemical priming. Chemical priming is believed to represent a promising strategy for mitigating abiotic stress in crop plants. Plants biosynthesize various compounds, such as phytohormones and other metabolites, to adapt to adverse environments. Research on artificially synthesized compounds has also resulted in the identification of novel compounds that improve abiotic stress tolerance. In this review, we summarize current knowledge of both naturally synthesized and artificial priming agents that have been shown to increase the abiotic stress tolerance of plants.